Four Thousand Hooks : A True Story of Fishing and Coming of Age on the High Seas of Alaska - Adams, Dean J. (Book collections on Project MUSE., 2012)
As Four Thousand Hooks opens, an Alaskan fishing schooner is sinking. It is the summer of 1972, and the sixteen-year-old narrator is at the helm. Backtracking from the gripping prologue, Dean Adams tells how he came to be a crew member on the Grant and unfolds a tale of adventure that reads like a novel-with drama, conflict, and resonant portrayals of halibut fishing, his ragtag shipmates, maritime Alaska, and the ambiguities of family life.